Host's Endogenous Caveolin-1 Expression is Downregulated in the Lung During Sepsis to Promote Cytoprotection. - Kataki, Agapi; Karagiannidis, Ioannis; Memos, Nikolaos; Koniaris, Efthymios; Antonakis, Pantelis; Papalois, Apostolos; Zografos, George C; Konstadoulakis, Manoussos M (Shock, 2018)
The present study focuses on the profile of "endogeneous" caveolin-1 protein in septic lung (CLP model).Caveolin-1, CD25, pP38, pAkt, and 14-3-3b protein expression profiles were studied using flow cytometry and immunohistochemistry 6, 12, 24, 36, and 48 h after sepsis induction. Cell viability was determined by 7-AAD staining and fibrosis by Masson trichrome stain. The effect of protein C zymogen concentrate (PC) on caveolin-1 expression was also investigated given that PC, once dissociated from caveolin-1, elicits a PAR-1-mediated protective signaling by forming a complex with endothelial protein C receptor (EPCR).CLP treatment increased lung inflammation and cell apoptosis. Fibrosis was apparent in vessels and alveoli. Caveolin-1+ cells presented reduced protein expression, especially 12 h post-CLP (P = 0.002). Immunohistochemistry revealed caveolin-1 positive expression mainly in regions with strong inflammatory reaction. Early induction of pP38+ cell population (P = 0.014) and gradual increase of CD25+ cells were also observed. Alternations in 14-3-3b expression related to apoptosis were apparent and accompanied by increased AKT phosphorylation activity late during sepsis progression.After PC administration, cell apoptosis was reduced (P = 0.004) and both the percentile and expression intensity of caveolin-1 positive cells were compromised (P = 0.009 and P = 0.027, respectively). 14-3-3b, CD25, and pP38 protein expression were decreased (P = 0.014, P = 0.004, and P = 0.007, respectively), whereas pAkt expression was induced (P = 0.032).The observed decline of endogenous caveolin-1 protein expression during sepsis implies its involvement in host's cytoprotective reaction either directly, by controlling caveolae population to decrease bacterial burden, or indirectly via regulating 14-3-3b-dependent apoptosis and EPCR-PAR-1-dependent protective signaling.
Keywords: Animals; apoptosis; Caveolin 1; Cytoprotection; Disease Models, Animal; Down-Regulation; Lung; Protein C; Rats; Rats, Wistar; Sepsis; signal transduction